TIME SERIES MODELLING OF HOSPITAL CENSUS: APPLICATION ON OUT PATIENT DEPARTMENT DATA OF AN AYURVEDIC SECONDARY CARE HOSPITAL - Tripathi, *Arunabh; Mitra, Achintya; Hazra, Jayram (International Journal of Ayurveda and Pharma Research, 2018)
The main objective of this paper is to fitt a curve on OPD data, for predicting the hospital OPD data. Four models were selected for curve fitting. All four models were fitted to old and new OPD patients for male and female separately. Models equations and coefficient of determination were calculated. Second order polynomial model was fitted well in all situations though exponential model was fitted well on old OPD patient data.